The Effect of Fruit, Vegetable, Fast Food Consumption, and Physical Activity on Waist Circumference in Adolescent Boys - Muddzalifah, Dewi; Laga Nur, Marselinus; Oematan, Grouse; Jutomo, Lewi (Pergizi Pangan DPD NTT, 2025)
Background: Central obesity in adolescents is a growing health problem that has the potential to cause various non-communicable diseases in the future. Objectives: This study aims to analyze the influence of fruit and vegetable consumption, fast food consumption, and physical activity on waist circumference among male adolescents in Kupang City. Methods: The study design used was quantitative with a cross-sectional approach and utilized secondary data from the Indonesian Health Survey (SKI) in Kupang City for the year 2023. The sample size consisted of 115 male adolescents aged 10–18 years selected from 66 census blocks. Data were analyzed using univariate and bivariate methods with the chi-square test. Results: The results showed that there was no significant effect of fruit consumption (p-value=0.771 < 0.05), vegetables (p-value=1.000 < 0.05), fast food (p-value=0.487 < 0.05), as well as moderate and vigorous physical activity (p-value=0.950 < 0.005) and (p-value=0.397 < 0.05) on waist circumference. Conclusions: The conclusion of this study is that, in addition to fruit, vegetable, fast food consumption, and physical activity, other factors such as genetics and lifestyle also play an important role in controlling waist circumference in adolescent males, thus requiring healthy lifestyle interventions from an early age.